Investigating the vapour transport phenomena inside the cathode gas diffusion layer media by controlling local temperature gradient inside an operating proton exchange membrane fuel cell. (1st January 2021) - Shigemasa, Kaito; Sato, Hayate; Otsuki, Yota; Kurosu, Masato; Araki, Takuto
Highlights: Correlation between temperature profile inside an operating PEMFC and its performance was investigated experimentally for the first time. In-house very fine sensor (6 μ m thick and 30 μ m wide) was fabricated and inserted into an operating PEMFC. Local temperature measurement and visualisation inside an operating PEMFC were performed simultaneously inside an X-ray CT machine. Vapour transport phenomena was discussed to reveal correlation between temperature profile and the PEMFC performance. Graphical abstract: Abstract: Water management is critical for the function of the proton exchange membrane fuel cell (PEMFC). The local through-thickness temperature gradient of the cathode gas diffusion layer (GDL) affect water management for a PEMFC. That has been known and been targeted for the discussion for several years. In this study, the effects of temperature gradient inside PEMFC was investigated by controlling it externally with a fine (testing diameter about 30 μ m) and thin (thickness about 6 μ m) thin-film thermocouple (TFTC), which has been developed using micro electromechanical system (MEMS) technology. In addition, X-ray computed tomography (CT) has been chosen as a method to visualise inside of an operating PEMFC. The simultaneously measurement of temperature gradient and liquid water distribution was firstly accomplished. In conclusion, in the case where the temperature of the cathode catalyst coated membrane (CCM) side is higher than that of the channel side, the PEMFC performance drastically decreased. The difference in PEMFC performance was caused by a difference the preferential sites for water condensation.